2018
DOI: 10.1155/2018/7954371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Valproate Monotherapy on the Oxidant‐Antioxidant Status in Mexican Epileptic Children: A Longitudinal Study

Abstract: Epilepsy is a neurological disorder that can produce brain injury and neuronal death. Several factors such as oxidative stress have been implicated in epileptogenesis. Valproic acid (VPA) is a widely used drug for the treatment of epilepsy, but the mechanisms underlying these benefits are complex and still not fully understood. The objective of this study was to evaluate, for the first time, the effects of VPA on the oxidant-antioxidant status in Mexican epileptic children before and after 6 or 12 months of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
2
14
0
3
Order By: Relevance
“…In addition, the number of seizures was significantly positively correlated with the levels of these oxidative stress markers. Furthermore, in this work, we showed that carbonyl levels are significantly negatively correlated with latency in the brain prefrontal cortex of rats treated with KA, consistent with the findings of another study on humans where we showed, for the first time, that protein oxidation (measured as 3-nitrotyrosine plasmatic levels) is significantly increased in epileptic children in comparison with the control children [20]. In another rat model, the authors also showed that PC content and lipid peroxidation levels are increased in the brain prefrontal cortex in the context of iron-induced epilepsy and that administration of dehydroepiandrosterone (DHEA), a corticosteroid hormone with antioxidant 13 Oxidative Medicine and Cellular Longevity properties, attenuates these effects, suggesting that the antioxidant improved performance on cognitive tasks and prevented behavioral alterations [61].…”
supporting
confidence: 92%
“…In addition, the number of seizures was significantly positively correlated with the levels of these oxidative stress markers. Furthermore, in this work, we showed that carbonyl levels are significantly negatively correlated with latency in the brain prefrontal cortex of rats treated with KA, consistent with the findings of another study on humans where we showed, for the first time, that protein oxidation (measured as 3-nitrotyrosine plasmatic levels) is significantly increased in epileptic children in comparison with the control children [20]. In another rat model, the authors also showed that PC content and lipid peroxidation levels are increased in the brain prefrontal cortex in the context of iron-induced epilepsy and that administration of dehydroepiandrosterone (DHEA), a corticosteroid hormone with antioxidant 13 Oxidative Medicine and Cellular Longevity properties, attenuates these effects, suggesting that the antioxidant improved performance on cognitive tasks and prevented behavioral alterations [61].…”
supporting
confidence: 92%
“…In contrast, 6-and 12-month valproate monotherapy increased activity of antioxidant enzymes (glutathione reductase, glutathione peroxidase, superoxide dismutase, and catalase) in 32 pediatric patients. Simultaneously, reduced levels of oxidative markers, such as malondialdehyde, hydrogen peroxide, 8-hydroxy-2-deoxyguanosine and 3-nitrotyrosine, were observed [1].…”
Section: Antiseizure Drugs and Epileptogenesismentioning
confidence: 94%
“…First-generation ASDs occurred rather disappointing in the aspect of neuroprotection and prevention of epileptogenesis, valproate showing some antiepileptogenic potential [1][2][3][4][5]. Moreover, this class of ASDs often enhances epilepsy aftermaths, impairing cognition and decreasing mood [32,33,38].…”
Section: Antiseizure Drugs and Epileptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Topiramate can inhibit free radical production, attenuate lipid peroxidation, and supporting the antioxidant redox system to protect pentylenetetrazol-induced brain injury [ 187 ]. In a recent study, it was shown that children with valproic acid monotherapy has significant antioxidant effects and decreases seizure activity [ 188 ]. Valproic acid may increase levels of glutathione and exert its neuroprotective effect [ 189 ].…”
Section: The Potentials Of Antioxidants In Status Epilepticusmentioning
confidence: 99%